Primary cutaneous CD4+ small- to medium-sized pleomorphic T-cell lymphoma: temporary remission by oral doxycycline - Toberer, Ferdinand; Hartschuh, Wolfgang; Hadaschik, Eva (JAMA dermatology, 2013)
In the recent World Health Organization-European Organisation for Research and Treatment of Cancer classification, primary cutaneous CD4+ small- to medium-sized pleomorphic T-cell lymphoma is listed as a provisional entity that is histopathologically characterized by pleomorphic CD3+/CD4+/CD8−/CD30− T lymphocytes. Clinically, it is characterized by solitary tumors mostly affecting the head and neck area and by an indolent clinical course with an estimated 5-year survival of about 60% to 80%. Currently, therapeutic options include topical or systemic treatment with glucocorticoids, local excision of solitary lesions, radiotherapy, and chemotherapy (eg, cyclophosphamide) in cases of aggressive clinical behavior or systemic disease.We present the case of a 21-year-old female patient with a 5-year history of a solitary, slowly growing tumor of the right cheek. Histopathologic findings revealed a primary cutaneous CD4+ small- to medium-sized pleomorphic T-cell lymphoma with an admixture of numerous CD20+ B cells representing almost half of the infiltrate. In this patient we achieved a temporary (13 months) complete remission of the lymphoma by oral treatment with doxycycline monohydrate, 200 mg per day.Doxycycline is a relatively nontoxic and well-tolerated oral agent and should be considered as a therapeutic option in primary cutaneous CD4+ small- to medium-sized pleomorphic T-cell lymphoma, especially in cases with a high percentage of B lymphocytes and no signs of systemic disease.
Im Titel ist das "+"-Zeichen hochgestellt
Gesehen am 07.02.2022